Collection of maples (Acer L.) of Ufa botanical garden - Ryazanova Nadezhda Alexandrovna (Hortus Botanicus, 2017)
The article includes information about the collection of maples of the Botanical Garden-Institute of Ufa Scientific Center: a list of taxa, indicating sections in accordance with the latest genus classification, distribution area, origin and description of the original material, introduction year and the number of specimen, as well as quick information about the condition and winter hardiness is listed.